MANUSIA DAN HISTORISITASNYA MENURUT MARTIN HEIDEGGER - Tjahyadi, Sindung (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractHeidegger viewed â€œfreedomâ€ and â€œtranscendenceâ€ (retrospective consciousness) as the element that determines â€œthe way of human existenceâ€ and also the human understanding of â€œhistoryâ€ radically. Philosophy of history is the main point ofHeideggerâ€™s philosophy. It is showed by his most fundamentalconcept of â€œtemporalityâ€. Heidegger so far developed the basiccharacteristic of relationship of â€œBeingâ€ (reality) and â€œtimeâ€(horizon) as a dialectical relationship. Because of his â€œpoeticâ€nuance, Heidegger often makes someone confused for his called for â€œBeingâ€ as a â€œpersonâ€, e.g., it as â€œthe giver of blessingâ€. Heidegger brings to the â€œtrueâ€ understanding that all philosophical inquiries start and end in the understanding of human being.Keywords: the way of being, being, history, human being